الفروق الفردية اللغوية العربية - Khoirun Nisa; Hadi Imaronah (Kilmatuna: Journal Of Arabic Education, 2021)
Difference is a common phenomenon, it is the sunatullah of His creatures, no two persons are the same in answering one question. That is, if everyone is equal in intelligence, then intelligence will be the one that distinguishes one another and so on. Likewise in language, especially Arabic, of course each individual has different abilities and advantages in language, because the ability of reason created is different by the Creator. As we know, language is one of several media to find one's excellence and personality, when someone speaks or talks about something, basically the content of the conversation is influenced by various elements related to genre, age, social environment, maturity of reason and so on. The success of a person's language is formed by the vocabulary or vocabulary for language. In contrast to written language, which usually has a lot of vocabulary, it is rarely used. The spoken language is limited by the number of vocabulary words, while the written language contains many of the vocabulary used in the language of reading and research.